Peran Burnout pada Keadilan Kompensasi, Beban Kerja, dan Turnover Intention Guru Inklusi kota Semarang - Afrida Yulia Mushaidillah; Edy Purwanto (Value : Jurnal Manajemen dan Akuntansi, 2026)
The high turnover intention among inclusive school teachers poses a serious challenge to the sustainability of educational services for students with special needs. This study aims to analyze the effect of compensation justice and workload on turnover intention, with burnout as an intervening variable among inclusive school teachers in Semarang City. This study employed an explanatory quantitative approach involving 115 respondents selected through purposive sampling from active inclusive school teachers. Data were collected using standardized questionnaires and analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that compensation justice does not directly affect turnover intention but has a significant and positive effect on burnout suggesting that higher perceptions of compensation justice are associated with higher levels of burnout among inclusive school teachers. Workload was found to have a positive and significant effect on both burnout and turnover intention. Burnout was also found to have a positive and significant effect on turnover intention; however, the mediating role of burnout on both pathways was not statistically confirmed. These findings imply that retention strategies for inclusive school teachers should encompass proportional workload management, adequate psychological support, and strengthening of professional commitment, and cannot rely solely on compensation improvements.